Interleukin-10-alveolar macrophage cell membrane-coated nanoparticles alleviate airway inflammation and regulate Th17/regulatory T cell balance in a mouse model - Li, Jun-Da; Yin, Jia (Frontiers in Immunology, 2023)
Background: Allergic airway disease (AAD) is a chronic disease characterized by airway inflammation, bronchoconstriction, and hyperresponsiveness. Although exogenous interleukin-10 (IL-10) alleviates allergic inflammation, it has a short half-life in vivo. Cell membrane-coated nanomaterials have been shown to protect therapeutic payloads and increase therapeutic efficacy. Objective: This study was aimed at investigating the efficacy of a novel macrophage-based nanoparticle drug for the treatment of house dust mite (HDM)-induced allergic airway diseases. Methods: IL-10-poly(lactic-co-glycolic acid (PLGA) nanoparticles were encapsulated in alveolar macrophage cell membranes. An allergic airway disease mouse model was established by repeated inhalation of HDM extracts. The mice were treated with free IL-10, IL-10-PLGA nanoparticles (IL10-NP), or IL-10-alveolar macrophage cell membrane-coated nanoparticles (IL10-AMNP). The therapeutic effects were evaluated by measuring airway hyperresponsiveness, lung inflammation, cytokine levels, and Treg-Th17 cell balance. Results: Compared to free IL-10, IL10-AMNP significantly reduced airway hyperresponsiveness and T-helper 2 (Th2)/Th17 cytokines and inhibited neutrophilia and eosinophilia recruitment into the airways of HDM-induced mouse models. Additionally, the balance between Tregs and Th17 cells was significantly improved in groups treated with IL10-AMNP. Conclusion: This study demonstrated that PLGA nanoparticle cores coated with alveolar macrophage cell membranes can effectively deliver therapeutic cytokines to the lungs and improve the homeostatic balance between Tregs and Th17 cells. These findings suggest that macrophage-based nanoparticle drugs represent a promising approach for treating allergic airway diseases.